Flour confectionery products of increased nutritional value - N. K. Lapteva; L. V. Mitkinykh (Аграрная наука Евро-Северо-Востока)
Studies on design of scientific and technological documentation for new flour confectionary with increased nutritional value are conducted in North-East Agricultural Research Institute. High attention is paid to using of rye raw material (rye flour and malt) for full or partial substitution of wheat flour with the purpose of broadening of production assortment. It is linked with the fact that rye has the lowest calories content of grain and products of its processing among all cereal crops, and contents much more minerals, microelements, vitamins, and fibers. Its grain contents more essential amino acids than wheat has. Raw materials of other cereal crops along with oil crops are used in new receipts too for heightening of these foodstuffs. Among new products there are documentations for cake “Osenny”, biscuit rolls “Niva” with jam and “Niva” with fruit butter, biscuits “Debyut”, “Stimul”, and “Trio”. New flour confectionaries are differed from existing analogues by heightened (by 23.1.155.6%) content of fibers and lowered (by 1.8.20.8%) energy value. Cake “Osenny”, rolls “Niva” with jam and “Niva” with fruit butter, biscuits “Trio” have high content of polyunsaturated fatty acids that are important for man health. Cake “Osenny” has 3.16 g of these acids per 100 g while its industrial analogue (cake “Sportivny”) has as low as twice content of polyunsaturated acids - 1.53 g / 100 g. Using of rye raw material in production of new confectionary will allow to broad assortment of foodstuff with high nutritional value, to lower cost of raw materials for production, to lower energy potential of diet that is important for rational health type of nutrition of modern human.